Stakeholder Networking and Institutional System Approaches in the Context of Sustainability for Smallholder Peatland Plantations - Ridha Rizki Novanda; Ellys Yuniarti; Redy Badruddin; Rahmi Yuristia; Achmad Amiruddin (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
This research investigates the challenges faced by smallholder oil palm plantations on peatlands in Mukomuko Regency. It focuses on stakeholder networking and institutional approaches to ensure the sector sustainability. Qualitative data was collected through interviews, focus group discussions (FGDs), and field observations, capturing stakeholder perspectives and experiences. Quantitative data was gathered via surveys targeting smallholder farmers and stakeholders, analyzing power, interest, and sentiment. Key data sources include farmers, the Village government, Agricultural Extension Officers (PPL), and the Replanting Chairperson. The data analysis employs a descriptive approach, incorporating the Total Weighting of Degree Among Actors method to evaluate the strength of stakeholder networks. This method highlights the collaboration, influence, and connectivity among stakeholders. The findings reveal that the Village government, particularly the Village Head and Secretary, plays a crucial role in promoting sustainability through collaboration. Strengthening stakeholder networks, including better coordination between the Village Head, Secretary, farmers, and extension officers, is recommended to enhance the sustainable management of oil palm plantations on peatlands.